2016
DOI: 10.5194/isprs-annals-iii-5-167-2016
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Robotic Inspection in Tunnels

Abstract: ABSTRACT:In this paper, an automatic robotic inspector for tunnel assessment is presented. The proposed platform is able to autonomously navigate within the civil infrastructures, grab stereo images and process/analyse them, in order to identify defect types. At first, there is the crack detection via deep learning approaches. Then, a detailed 3D model of the cracked area is created, utilizing photogrammetric methods. Finally, a laser profiling of the tunnel's lining, for a narrow region close to detected crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…Protopapadakis et al 31 introduced an integrated automatic platform for road and railway tunnel inspection. Based on this platform, a three-layer convolutional neural network (CNN) taking 9 × 9 patches as input was used as feature extract.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Protopapadakis et al 31 introduced an integrated automatic platform for road and railway tunnel inspection. Based on this platform, a three-layer convolutional neural network (CNN) taking 9 × 9 patches as input was used as feature extract.…”
Section: Related Workmentioning
confidence: 99%
“…They showed that CNN is good at detecting thin cracks under varying lighting conditions and is more robust to noise than any traditional methods. As examples of the early deep-learning-based methods, Protopapadakis et al 31 and Cha et al 13 generated a single label for a patch, and sliding window techniques were applied to scan through the whole image. This kind of techniques could only provide information about whether a patch include cracks or not.…”
Section: Related Workmentioning
confidence: 99%
“…Following this success, CNN has revolutionised the field of computer vision and become a state of the art for recognition and detection purpose [5]. In addition, it has been utilised in a wide range of application such as image classification for a large number of classes [9-11], traffic sign recognition [12], medical object classification [13][14][15], face recognition [16,17], and damage detection in structures [18][19][20][21]. In addition to automatic feature extraction, CNN can produce excellent performance for complex image recognition task due to the capability of CNN in exploiting the local spatial correlation between pixels in the image [5].…”
Section: Bridge Load Testingmentioning
confidence: 99%
“…In recent years, relevant scholars have researched the application of deep learning in the detection of cracks at tunnel linings. References [ 25 , 26 , 27 ] achieved good results in terms of accuracy and efficiency. Nevertheless, deep learning algorithms require a large number of labeled images of training, and these images are not easy to obtain.…”
Section: Introductionmentioning
confidence: 99%